AgBr / Co / NiBr2 composite material catalyst as well as preparation method and application thereof
The AgBr/Co/NiBr2 composite catalyst addresses the limitations of existing photocatalysts by forming a Type-Ⅱ heterojunction and leveraging Co nanoparticles for enhanced charge separation and visible light absorption, achieving high toluene degradation efficiency with cost-effective synthesis.
Patent Information
- Application Number
- CN202510791066.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-13
- Publication Date
- 2025-07-15
- Estimated Expiration
- 2045-06-13
AI Technical Summary
The existing photocatalytic materials have problems such as low visible light utilization, high carrier recombination rate, poor cycle stability, and complex and expensive preparation methods of traditional composite materials.
AgBr/Co/NiBr2 composite materials were prepared by three-step method, forming a heterojunction structure and Co nanoparticles synergistically, broadening the light absorption range and improving the photogenerated carrier separation efficiency. The preparation process was simplified by using ethylene glycol solvent, ammonia precipitation method and H2 reduction method, and reducing costs.
It significantly improves the visible light absorption range and photogenerated carrier separation efficiency, achieves high-efficiency photocatalytic degradation of toluene, with a degradation rate of up to 90%, and maintains high activity under low temperature and low pressure. It is suitable for low-concentration industrial wastewater treatment.
Smart Images

Figure CN120305990A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts, and particularly relates to an AgBr / Co / NiBr2 composite catalyst, a preparation method thereof, and an application thereof. Background Art
[0002] With the annual increase in the discharge of organic pollutants (such as toluene) in industrial wastewater, the development of efficient and stable photocatalytic materials has become a research hotspot in the field of environmental governance. Traditional photocatalytic materials (such as TiO2, ZnO, etc.) have problems such as low visible light utilization rate, high carrier recombination rate, and poor cycle stability. In recent years, nickel-based oxides (such as NiO) have been used to modify photocatalysts due to their unique electronic structure. Chinese invention patent CN113441148A discloses a catalytic material for improving the biodegradability of petrochemical wastewater, which includes the following raw materials in parts by weight: 10-20 parts of sludge powder, 5-10 parts of Fe3O4, 1-2 parts of bentonite, 1-2 parts of a mixture of nickel oxide and copper oxide, 1-2 parts of MnO2, and 0.2-0.5 parts of ammonium bicarbonate. The preparation method is simple and easy to scale up. Only by sintering dehydrated and dried sludge with metals or metal oxides such as iron, manganese, copper, and nickel at high temperature, a porous composite material can be obtained, and the activation of biomass carbon and the loading of metal particles are realized synchronously during the cracking process, but its catalytic efficiency is still limited. Chinese invention patent CN111992008A discloses a method for catalytically enhancing the degradation of toluene by low-temperature plasma, which belongs to the technical field of catalytic degradation of toluene in organic waste gas. Using toluene as the waste gas, the degradation of toluene in organic waste gas is realized through a simple process of preparing MnO X / Al2O3 catalyst, debugging a low-temperature plasma reactor, catalytically enhancing the degradation of toluene by low-temperature plasma, and blowing off the tail gas. In the prior art, some studies have constructed composite materials to synergistically improve the photocatalytic performance, but the preparation methods mostly involve complex template methods or noble metal loading, resulting in cumbersome processes and high costs. Summary of the Invention
[0003] The present invention provides an AgBr / Co / NiBr2 composite catalyst, a preparation method thereof, and an application thereof. The preparation method is simple and low-cost, and has good catalytic performance.
[0004] The technical solution of the present invention is as follows: In the first aspect, a preparation method of an AgBr / Co / NiBr2 composite catalyst is disclosed, which includes the following steps: 1) Preparation of NiBr2: Add nickel acetate to ethylene glycol solvent and stir to form a transparent solution; add KBr to the solution and stir until KBr is completely dissolved; then add ammonia water with a mass concentration of 4%-8% to the mixed solution, stir at 20-30 °C for 4-6 h, dry at 60-70 °C for 24-48 h, and calcine at 500-600 °C for 3-5 h to obtain the product NiBr2; 2) Preparation of Co / NiBr2 composite material: Disperse the product NiBr2 obtained in step 1) in water, ultrasonically disperse it evenly, add cobalt nitrate to it, stir and react for 30-40 min, centrifuge, collect the precipitate, wash, dry, calcine in a muffle furnace, and then put it into a tubular furnace and introduce H2 for reduction to finally obtain the Co / NiBr2 composite material, and the particle size of Co nanoparticles is 5-8 nm; 3) Preparation of AgBr / Co / NiBr2 composite material: Disperse the Co / NiBr2 composite material in ethanol, ultrasonically disperse it evenly, add AgNO3 to it, stir for 10-20 min, then add KBr to it, place it in a water bath at 80-90 °C and react until the ethanol is completely evaporated, collect the solid product and calcine it at 150-200 °C for 3-6 h to obtain the AgBr / Co / NiBr2 composite material catalyst.
[0005] Preferably, in step 1), the mass-volume ratio of nickel acetate, KBr and ethylene glycol is (3-5) g: (2.8-4.8) g: (25-30) mL.
[0006] Preferably, in step 1), the volume ratio of ammonia water to ethylene glycol is 1:3-2:1.
[0007] Preferably, in step 2), the mass-volume ratio of cobalt nitrate and water is (10-20) g: (30-50) mL.
[0008] Preferably, in step 2), the drying is carried out in an oven at 60-70 °C for 8-10 h, the calcination temperature in step 2) is 200-300 °C, the time is 6-10 h, and the H2 reduction temperature is 200-300 °C, and the time is 4-5 h.
[0009] Preferably, the reaction in step 2) is carried out in an N2 or Ar atmosphere.
[0010] Preferably, in step 3), the mass-volume ratio of AgNO3, KBr and ethanol is (2-5) g: (1.4-3.5) g: (10-15) mL.
[0011] In the second aspect, an AgBr / Co / NiBr2 composite material catalyst prepared by the described preparation method is disclosed.
[0012] Thirdly, the application of the AgBr / Co / NiBr2 composite catalyst in photocatalytic degradation of toluene in wastewater is disclosed, including the following steps: a) The prepared catalyst is placed in a quartz glass tube of a photoreactor. The set temperature of the photoreactor is 20 - 30 °C and the pressure is 0.1 - 0.3 MPa; b) Add photocatalytic degradation wastewater into the quartz tube. Seal the quartz tube. Under dark conditions, introduce helium gas into the liquid film photoreactor. The flow rate of helium gas is 90 - 110 mL / min, and the introduction time of helium gas is 20 - 40 min. Then discharge the gas in the reactor; c) Under the irradiation of a xenon lamp with an irradiation power of 300 - 400 W, after reacting for 5 - 10 h, measure the concentration of toluene before and after the reaction.
[0013] The AgBr / Co / NiBr2 composite was successfully synthesized by a simple alcoholysis method. NiBr2 has a narrow bandgap (~1.97 eV). After being combined with AgBr (bandgap ~2.6 eV), the light absorption range is broadened to the visible light region. The energy band positions of AgBr and NiBr2 are staggered to form a step (Type-II) energy band structure. Under the action of the built-in electric field, photo-generated electrons migrate from the conduction band of AgBr to the conduction band of NiBr2, while photo-generated holes migrate from the valence band of NiBr2 to the valence band of AgBr, thus inhibiting the recombination of photo-generated carriers. At the same time, Co acts as an electron medium or bridge for charge transfer in the photocatalytic system, accelerating the transfer of photo-generated electrons from AgBr → Co → NiBr2 and further improving the charge separation efficiency. In addition, the local surface plasmon resonance (LSPR) of Co nanoparticles generates a strong electromagnetic field in the visible light region (especially 500 - 700 nm), significantly enhancing the light absorption of the composite. Therefore, the enhancement of photocatalytic activity is attributed to the formation of the Type-II heterojunction, the electron bridge of Co nanoparticles and their induced LSPR synergistic effect.
[0014] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention has high photocatalytic performance. The AgBr / Co / NiBr2 composite prepared by a three-step method forms a synergistic effect of a heterojunction structure (AgBr and NiBr2) and Co nanoparticles, significantly improving the visible light absorption range (400 - 800 nm) and the separation efficiency of photo-generated carriers. Experiments show that the degradation rate of toluene by this material can reach 90% under the irradiation of a xenon lamp.
[0015] 2. The present invention optimizes the preparation process to reduce production costs. The ethylene glycol solvent and ammonia precipitation method simplifies the synthesis steps of NiBr2 and avoids high-temperature and high-pressure conditions; the H2 reduction method precisely controls the loading amount of Co nanoparticles and reduces the usage of precious metals; the ethanol evaporation method realizes uniform coating of AgBr and avoids complex post-treatment.
[0016] 3. It still maintains high activity under low temperature (20 - 30 °C) and low pressure (0.1 - 0.3 MPa) conditions and is suitable for the treatment scenario of low-concentration industrial wastewater. Description of the Drawings
[0017] Figure 1 It is the morphology diagram of the catalyst prepared in Example 1 of the present invention.
[0018] Figure 2 It is the morphology diagram of the catalyst prepared in Example 1 of the present invention under a high-power microscope.
[0019] Figure 3 It is the XRD diagram of the catalyst prepared in Example 1 of the present invention. Detailed Embodiments
[0020] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0021] Example 1 The AgBr / Co / NiBr2 composite material catalyst described includes a NiBr2 nanoflower carrier, loaded Co nanoparticles, and AgBr, where the Co loading amount is 5 wt% of the total mass of the catalyst, and the AgBr loading amount is 2 wt% of the total mass of the catalyst.
[0022] The preparation method of the AgBr / Co / NiBr2 composite material catalyst includes the following steps: 1) Preparation of NiBr2: Add 5 g of nickel acetate to 30 mL of ethylene glycol solvent and stir to form a transparent solution; add 4.8 g of KBr to the solution and stir until the KBr is completely dissolved, then add 56 mL of ammonia water with a mass concentration of 7% to the mixed solution, stir at 30 °C for 4 h, dry at 60 °C for 48 h, and calcine at 500 °C for 5 h to obtain the product NiBr2; 2) Preparation of Co / NiBr2 composite material: Disperse the product NiBr2 from step 1) into 50 mL of water, ultrasonically disperse it evenly, add 20 g of cobalt nitrate to it, carry out the reaction in an N2 atmosphere, stir for 35 min, centrifuge, collect the precipitate, wash it 3 times with deionized water, dry it in an oven at 65 °C for 9 h, calcine it in a muffle furnace at 250 °C for 8 h, then put it into a tubular furnace and pass H2 for reduction, with the temperature being 280 °C and the time being 4 h, finally obtaining the Co / NiBr2 composite material, and the particle size of Co nanoparticles is 7 nm; 3) Preparation of AgBr / Co / NiBr2 composite material: Disperse the above Co / NiBr2 composite material into 12 mL of ethanol, ultrasonically disperse it evenly, add 3 g of AgNO3 to it, stir for 15 min, then add 2 g of KBr to it, place it in a water bath at 85 °C and react until the ethanol completely evaporates, collect the solid product and calcine it at 180 °C for 4 h to obtain the AgBr / Co / NiBr2 composite material catalyst. The morphology diagrams of the catalyst are as shown in Figure 1 and Figure 2 shown, and the XRD diagram is as shown in Figure 3 shown; Figure 1 It shows that the material is in the shape of nanoflowers, Figure 2 under high magnification, it shows the particle distribution of Co and the coating of AgBr, Figure 3 the XRD diagram of
[0023] shows the existence of three phases of AgBr, Co and NiBr2. The application of the above-mentioned AgBr / Co / NiBr2 composite material catalyst in the photocatalytic degradation of toluene in wastewater includes the following steps: a) Place 1 g of the prepared catalyst in the quartz glass tube of the photoreactor, and the set temperature of the photoreactor is 25 °C and the pressure is 0.2 MPa; b) Add photocatalytic degradation wastewater to the quartz tube, seal the quartz tube, under dark conditions, pass helium gas into the liquid film photoreactor, the flow rate of helium gas is 100 mL / min, the passing time of helium gas is 30 min, and discharge the gas in the reactor;
[0024] Example 2 The above-mentioned AgBr / Co / NiBr2 composite material catalyst includes a NiBr2 nanoflower carrier, supported Co nanoparticles and AgBr, wherein the Co loading is 7 wt% of the total mass of the catalyst, and the AgBr loading is 5 wt% of the total mass of the catalyst.
[0025] The preparation method of the above-mentioned AgBr / Co / NiBr2 composite material catalyst includes the following steps: 1) Preparation of NiBr2: 3 g of nickel acetate was added to 25 mL of ethylene glycol solvent and stirred to form a transparent solution; 3 g of KBr was added to the solution and stirred until KBr was completely dissolved. Then, 25 mL of ammonia water with a mass concentration of 4% was added to the mixed solution, and the mixture was stirred at 20 °C for 5 h, dried at 65 °C for 30 h, and calcined at 550 °C for 4 h to obtain the product NiBr2; 2) Preparation of Co / NiBr2 composite material: The product NiBr2 obtained in step 1) was dispersed in 30 mL of water and ultrasonically dispersed evenly. 10 g of cobalt nitrate was added thereto, and the reaction was carried out in an Ar atmosphere, stirred for 30 min, centrifuged, the precipitate was collected, washed 3 times with deionized water, dried in an oven at 60 °C for 10 h, calcined in a muffle furnace at 200 °C for 10 h, and then placed in a tubular furnace and reduced by introducing H2 at a temperature of 200 °C for 5 h. Finally, the Co / NiBr2 composite material was obtained, and the particle size of Co nanoparticles was 5 nm; 3) Preparation of AgBr / Co / NiBr2 composite material: The above Co / NiBr2 composite material was dispersed in 10 mL of ethanol and ultrasonically dispersed evenly. 2 g of AgNO3 was added thereto and stirred for 10 min. Then, 1.4 g of KBr was added thereto, and the mixture was placed in a water bath at 90 °C and reacted until the ethanol was completely evaporated. The solid product was collected and calcined at 150 °C for 6 h to obtain the AgBr / Co / NiBr2 composite material catalyst.
[0026] Application of the described AgBr / Co / NiBr2 composite material catalyst in photocatalytic degradation of toluene in wastewater, including the following steps: a) 1 g of the prepared catalyst was placed in the quartz glass tube of the photoreactor. The set temperature of the photoreactor was 20 °C and the pressure was 0.1 MPa; b) Photocatalytic degradation wastewater was added to the quartz tube, and the quartz tube was sealed. Under dark conditions, helium gas was introduced into the liquid film photoreactor at a flow rate of 90 mL / min for 40 min, and the gas in the reactor was discharged; c) Under the irradiation of a xenon lamp with an irradiation power of 300 W, after reacting for 10 h, the concentration of toluene before and after the reaction was measured.
[0027] Example 3 The described AgBr / Co / NiBr2 composite material catalyst includes a NiBr2 nanoflower carrier, supported Co nanoparticles and AgBr, wherein the Co loading is 10 wt% of the total mass of the catalyst, and the AgBr loading is 6 wt% of the total mass of the catalyst.
[0028] The preparation method of the AgBr / Co / NiBr2 composite material catalyst includes the following steps: 1) Preparation of NiBr2: 4 g of nickel acetate was added to 30 mL of ethylene glycol solvent and stirred to form a transparent solution; 3.8 g of KBr was added to the solution and stirred until KBr was completely dissolved, then 10 mL of ammonia water with a mass concentration of 8% was added to the mixed solution, stirred at 25 °C for 6 h, dried at 70 °C for 24 h, and calcined at 600 °C for 3 h to obtain the product NiBr2; 2) Preparation of Co / NiBr2 composite: The product NiBr2 from step 1) was dispersed in 35 mL of water, ultrasonically dispersed evenly, 12.5 g of cobalt nitrate was added thereto, carried out in an Ar atmosphere, stirred and reacted for 40 min, centrifuged, the precipitate was collected, washed 3 times with deionized water, dried in an oven at 70 °C for 8 h, calcined in a muffle furnace at 300 °C for 6 h, and then put into a tubular furnace and reduced by passing H2, the temperature was 300 °C, and the time was 4.5 h, finally obtaining the Co / NiBr2 composite, and the particle size of Co nanoparticles was 8 nm; 3) Preparation of AgBr / Co / NiBr2 composite: The above Co / NiBr2 composite was dispersed in 15 mL of ethanol, ultrasonically dispersed evenly, 5 g of AgNO3 was added thereto, stirred for 10 min, then 3.5 g of KBr was added thereto, placed in an 80 °C water bath and reacted until the ethanol was completely evaporated, the solid product was collected and calcined at 200 °C for 5 h to obtain the AgBr / Co / NiBr2 composite catalyst.
[0029] Application of the described AgBr / Co / NiBr2 composite catalyst in photocatalytic degradation of toluene in wastewater, including the following steps: a) 1 g of the prepared catalyst was placed in the quartz glass tube of the photoreactor, the set temperature of the photoreactor was 30 °C, and the pressure was 0.3 MPa; b) Photocatalytic degradation wastewater was added to the quartz tube, the quartz tube was sealed, under dark conditions, helium gas was introduced into the liquid film photoreactor, the flow rate of helium gas was 110 mL / min, the introduction time of helium gas was 20 min, and the gas in the reactor was discharged; c) Under the irradiation of a xenon lamp, the irradiation power of the xenon lamp was 350 W, after reacting for 5 h, the concentration of toluene before and after the reaction was measured.
[0030] Comparative Example 1 Different from Example 1, in this comparative example, only NiBr2 was prepared, and Co and AgBr were not loaded.
[0031] Comparative Example 2 Different from Example 1, in this comparative example, only the Co / NiBr2 composite was prepared, and AgBr was not loaded.
[0032] Comparative Example 3 Different from Example 1, in this comparative example, AgBr / NiBr2 was prepared by the following method: 1) Preparation of NiBr2: 5 g of nickel acetate was added to 30 mL of ethylene glycol solvent and stirred to form a transparent solution; 4.8 g of KBr was added to the above solution and stirred until the KBr was completely dissolved. Then, 56 mL of ammonia water with a mass concentration of 7% was added to the above mixed solution, stirred at 30 °C for 4 h, dried at 60 °C for 48 h, and calcined at 500 °C for 5 h to obtain the product NiBr2; 2) Preparation of AgBr / NiBr2 composite material: The above NiBr2 was dispersed in 12 mL of ethanol, ultrasonically dispersed evenly, 3 g of AgNO3 was added thereto, stirred for 15 min, then 2 g of KBr was added thereto, placed in an 85 °C water bath and reacted until the ethanol was completely evaporated. The solid product was collected and calcined at 250 °C for 4 h to obtain the AgBr / NiBr2 composite material catalyst.
[0033] Comparative Example 4 Different from Example 1, in this comparative example, concentrated ammonia water with a mass concentration of 25% was added, and the remaining preparation methods and steps were the same as those in Example 1.
[0034] Comparative Example 5 Different from Example 1, in this comparative example, step 2) was carried out in air, and the remaining preparation methods and steps were the same as those in Example 1.
[0035] Comparative Example 6 Different from Example 1, in this comparative example, the addition amount of silver nitrate in step 3) was 5.2 g, and the remaining preparation methods and steps were the same as those in Example 1.
[0036] Comparative Example 7 The preparation method of the composite material catalyst includes the following steps: 1) Preparation of NiBr2: 5 g of nickel acetate was added to 30 mL of ethylene glycol solvent and stirred to form a transparent solution; 4.8 g of KBr was added to the above solution and stirred until the KBr was completely dissolved. Then, 56 mL of ammonia water with a mass concentration of 7% was added to the above mixed solution, stirred at 30 °C for 4 h, dried at 60 °C for 48 h, and calcined at 500 °C for 5 h to obtain the product NiBr2; 2) Preparation of AgBr / NiBr2 composite material: The above NiBr2 composite material was dispersed in 12 mL of ethanol, ultrasonically dispersed evenly, 3 g of AgNO3 was added thereto, stirred for 15 min, then 2 g of KBr was added thereto, placed in an 85 °C water bath and reacted until the ethanol was completely evaporated. The solid product was collected and calcined at 180 °C to obtain the AgBr / NiBr2 composite material catalyst; 3) Preparation of Co / AgBr / NiBr2 composite material: Disperse the product of step 2) into 50 mL of water, ultrasonically disperse it evenly, add 20 g of cobalt nitrate to it, carry out the reaction in an N2 atmosphere, stir for 35 min, centrifuge, collect the precipitate, wash it 3 times with deionized water, dry it in an oven at 65 °C for 9 h, calcine it in a muffle furnace at 250 °C for 8 h, then put it into a tubular furnace and pass H2 for reduction, with the temperature being 280 °C and the time being 4 h, and finally obtain the composite material.
[0037] Perform performance detection on the catalysts prepared in the examples and comparative examples, and the detection results are shown in Table 1.
[0038] Table 1 Detection results of catalyst performance
[0039] It can be seen from Table 1 that the average specific surface area and average pore diameter of the catalysts prepared in the present invention are relatively large, and the crushing strength is relatively large, which is more conducive to improving the catalytic performance.
[0040] Use the catalysts prepared in the above examples and comparative examples for photocatalytic degradation of toluene. The degradation method in the comparative example is the same as that in Example 1, and the detection results are shown in Table 2.
[0041]
[0042] η is the degradation rate of toluene, M 反应初 and M 反应后 are the toluene concentration before the reaction and the toluene concentration after the reaction, respectively.
[0043] Table 2 Detection results of photocatalytic degradation of toluene
[0044] Comparative example 1 only contains NiBr2, without loading Co and AgBr. The carrier recombination rate is high, but the plasma resonance effect of Co nanoparticles is lacking, and the visible light absorption cannot be enhanced; no AgBr / NiBr2 heterojunction is formed, resulting in the rapid recombination of photo-generated electron-hole pairs.
[0045] Comparative example 2 is Co / NiBr2, without loading AgBr. Although Co / NiBr2 has the electron-mediated effect of Co, the energy band matching between AgBr and NiBr2 is lacking, and a Type-II heterojunction cannot be formed.
[0046] Comparative example 3 is AgBr / NiBr2, without loading Co. Although the AgBr / NiBr2 heterojunction expands the light absorption range, no Co nanoparticles are introduced, and the local light field cannot be enhanced by LSPR. The lack of Co leads to insufficient excitation intensity of photo-generated electrons and limited charge separation efficiency.
[0047] In Comparative Example 4, a high ammonia water concentration leads to agglomeration, reducing the specific surface area, resulting in a decrease in active sites. It becomes difficult for reactant molecules to contact the catalyst surface, and the catalytic efficiency decreases.
[0048] In Comparative Example 5, O2 in the air causes the oxidation of Co nanoparticles to CoO / Co3O4, losing the electron-mediated function of metallic Co. The oxidized Co becomes a recombination center, accelerating the recombination of electron-hole pairs and significantly reducing the catalytic activity.
[0049] In Comparative Example 6, an excessive amount of AgNO3 (0.6 g) generates too much AgBr, and the van der Waals force between particles causes agglomeration. AgBr covers the surface active sites of Co / NiBr2, hindering the adsorption of reactants and the photoexcitation process.
[0050] In Comparative Example 7, AgBr is loaded first and then Co is loaded, resulting in poor contact between Co and the AgBr / NiBr2 interface, interrupting the electron transfer path. The synergistic effect between the heterojunction and Co weakens, and the charge separation efficiency decreases.
Claims
1. Preparation method of AgBr / Co / NiBr2 composite material catalyst, characterized in that, It includes the following steps: 1) Preparation of NiBr2: Add nickel acetate to ethylene glycol solvent and stir to form a transparent solution; add KBr to the solution and stir until KBr is completely dissolved; then add ammonia water with a mass concentration of 4%-8% to the mixed solution, stir at 20-30 °C for 4-6 h, dry at 60-70 °C for 24-48 h, and calcine at 500-600 °C for 3-5 h to obtain the product NiBr2; 2) Preparation of Co / NiBr2 composite material: Disperse the product NiBr2 obtained in step 1) in water, ultrasonically disperse it evenly, add cobalt nitrate to it, stir and react for 30-40 min, centrifuge, collect the precipitate, wash, dry, calcine in a muffle furnace and then put it into a tubular furnace and pass H2 for reduction to finally obtain the Co / NiBr2 composite material; 3) Preparation of AgBr / Co / NiBr2 composite material: Disperse the Co / NiBr2 composite material in ethanol, ultrasonically disperse it evenly, add AgNO3 to it, stir for 10-20 min, then add KBr to it, place it in a water bath at 80-90 °C and react until the ethanol is completely evaporated, collect the solid product and calcine it at 150-200 °C for 3-6 h to obtain the AgBr / Co / NiBr2 composite material catalyst.
2. The preparation method of the AgBr / Co / NiBr2 composite material catalyst according to claim 1, characterized in that, In step 1), the mass-volume ratio of nickel acetate, KBr and ethylene glycol is (3-5) g: (2.8-4.8) g: (25-30) mL.
3. The preparation method of the AgBr / Co / NiBr2 composite material catalyst according to claim 1, characterized in that, In step 1), the volume ratio of ammonia water to ethylene glycol is 1:3 - 2:
1.
4. The preparation method of the AgBr / Co / NiBr2 composite material catalyst according to claim 1, characterized in that, In step 2), the mass-volume ratio of cobalt nitrate and water is (10-20) g: (30-50) mL.
5. The preparation method of the AgBr / Co / NiBr2 composite catalyst according to claim 1, characterized in that, In step 2), the drying is carried out in an oven at 60-70 °C for 8-10 h, the calcination temperature in step 2) is 200-300 °C, the time is 6-10 h, and the H2 reduction temperature is 200-300 °C, the time is 4-5 h.
6. The preparation method of the AgBr / Co / NiBr2 composite material catalyst according to claim 1, characterized in that, The reaction in step 2) is carried out in an N2 or Ar atmosphere.
7. The preparation method of the AgBr / Co / NiBr2 composite material catalyst according to claim 1, wherein, In step 3), the mass-volume ratio of AgNO3, KBr and ethanol is (2-5) g: (1.4-3.5) g: (10-15) mL.
8. The AgBr / Co / NiBr2 composite material catalyst prepared by the preparation method according to any one of claims 1-7.
9. Use of the AgBr / Co / NiBr2 composite catalyst as described in claim 8 in the photocatalytic degradation of toluene in wastewater, characterized in that, It includes the following steps: a) Place the prepared catalyst in the quartz glass tube of the photoreactor, the set temperature of the photoreactor is 20-30 °C, and the pressure is 0.1-0.3 MPa; b) Add photocatalytic degradation wastewater to the quartz tube, seal the quartz tube, and under dark conditions, pass helium into the liquid film photoreactor, the flow rate of helium is 90-110 mL / min, the helium passing time is 20-40 min, and discharge the gas in the reactor; c) Under the irradiation of a xenon lamp, the irradiation power of the xenon lamp is 300-400 W, after reacting for 5-10 h, measure the concentration of toluene before and after the reaction.
Citation Information
Patent Citations
Ag / AgBr / NH2-MIL-125 (Ti) composite material as well as in-situ preparation method and application thereof
CN109999916A
Magnetic Ag / AgBr / LaFeO3 composite photocatalyst and preparation method thereof
CN114100642A
AgBr-Co3O4-BiOBr composite material as well as preparation method and application thereof
CN114160174A
Fe2O3-La2O3-Rh2O3-coated HNixS composite material, preparation method thereof and application of Fe2O3-La2O3-Rh2O3-coated HNixS composite material in wastewater treatment
CN118847157A
TiO2 / Co3O4 / AgBr ternary heterojunction composite material as well as preparation method and application thereof
CN119633860A